Analisis Finansial Dan Kelembagaan Usahatani Tanaman Jeruk - Suharyon Suharyon; Firdaus Firdaus; Erwan Wahyudi (Jurnal Agribis, 2022)
The challenges to agriculture are more complex, including how to meet food needs and food self-sufficiency. The problems faced today is related to; limited resources of land, air, infrastructure, production facilities and infrastructure, access to finance and institutions that are still not conducive. One of the efforts that can eliminate these problems is through the study of the development of a comprehensive integrated agricultural area. This study was conducted in Bunga Tanjung Village, Betara District, Tanjung Jabung Barat Regency. The high cost is thought to be one of the causes of the low production of citrus farming. Efforts to increase production are currently experiencing challenges to the existence of doubts about the economic feasibility which causes a decrease in the interest in farmers to continue farming. The data collected to include primary and secondary data, as well as the condition of the study area, population demography, social and economic potential. Primary data was taken using a survey technique, namely interviewing farmers and key information using a questionnaire. Data analysis techniques include tabulation analysis used to understand the economic conditions of farmers' farming, economic feasibility analysis using the R/C ratio. The results of this study indicate that citrus productivity is increased by applying environmentally friendly cultivation technology by fertilizing, controlling pests and diseases, removing water shoots, pruning forms and pruning unproductive branches.